Perancangan UI/UX Webinar Booking Terhadap Kepuasan Pengguna Menggunakan Metode Design Thinking - Rachma Wukir Purwitasari; Purnama Dileon Yamora Nainggolan; Novi Rahmawati; Faisal Dharma Adhinata; Nur Ghaniaviyanto Ramadhan (JURIKOM (Jurnal Riset Komputer), 2021)
In order to meet user needs, designing an exemplary user interface requires in-depth knowledge of design principles and guidelines and an understanding of the multi-component design space. Multi-components are the image parts that can be used, their layout options, and visual effects options. This research was conducted to meet user needs. With the Design Thinking method, we can find out the user's needs and adjust to the user's interests. With the Webinar Booking application, it is hoped to be a solution for today's life